MASS CULTURE IN A DISCOURSE OF POSTMODERN - Кононенко, О. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Contradictory and influential phenomenon of mass culture in modern society and its versification in a discourse of postmodern is analyzed.